2011
DOI: 10.1002/eji.201142108
|View full text |Cite
|
Sign up to set email alerts
|

Natalizumab treatment perturbs memory‐ and marginal zone‐like B‐cell homing in secondary lymphoid organs in multiple sclerosis

Abstract: Natalizumab, an antibody against the a4 subunit of a4 integrins, has been approved for multiple sclerosis (MS) therapy based on its high efficacy and safety profile. However, natalizumab has been associated with the development of progressive multifocal leukoencephalopathy (PML), a disorder caused by JC virus (JCV) infection. In order to improve our understanding of the mechanism of action of natalizumab and to identify possible risk factors for PML development, we have characterized in detail the cell blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
100
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 102 publications
(111 citation statements)
references
References 42 publications
9
100
1
1
Order By: Relevance
“…Instead, by using the TREC and KREC assay we found that newly produced T and B lymphocytes were significantly increased in peripheral blood of patients treated for 6 and 12 months with natalizumab, thus indicating that the drug may influence the lymphocyte release from production sites. The increased production of new T and B lymphocytes was confirmed by flow cytometry that also demonstrated an augmented number of RTE and naïve CD4 + cells in treated patients while, as also shown by Planas et al [6], the percentage of these cell subsets remained unmodified.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Instead, by using the TREC and KREC assay we found that newly produced T and B lymphocytes were significantly increased in peripheral blood of patients treated for 6 and 12 months with natalizumab, thus indicating that the drug may influence the lymphocyte release from production sites. The increased production of new T and B lymphocytes was confirmed by flow cytometry that also demonstrated an augmented number of RTE and naïve CD4 + cells in treated patients while, as also shown by Planas et al [6], the percentage of these cell subsets remained unmodified.…”
Section: Discussionsupporting
confidence: 68%
“…Nevertheless, the majority of B cells in peripheral blood of treated patients were unswitched and switched memory B cells, which are known to undergo an antigen-independent (homeostatic) proliferation [14]. However, the comparable average number of B-cell divisions we have found before and after therapy supports the hypothesis that the natalizumab-induced increase of memory B cells is due to an inhibited retention in the spleen [6] more than a peripheral proliferation.…”
Section: Discussionmentioning
confidence: 50%
See 2 more Smart Citations
“…The effect of natalizumab on lymphocyte subpopulations is not fully defined, although it has been described that memory T-cells would be increased in peripheral blood and would induce changes in memory B-cells (90)(91)(92). Moreover, natalizumab treatment interferes with the mechanisms of bone marrow egress of hematopoietic stem cells, inducing an increase of CD34 + cells in peripheral blood, specifically lymphoid progenitors, transitional B-cells, and RTEs (17,91,(93)(94)(95)(96)(97).…”
Section: Natalizumabmentioning
confidence: 99%